Study on Canopy Interception Characteristics of Six Landscape Shrub Plants - Weiye ZHU; Bing XIAO; Ping CHEN; Xiulan SHI; Danlin ZHENG; Ruihong HAN (Guangdong nongye kexue, 2022)
【Objective】Canopy interception characteristics of six shrub plants used for landscaping in Guangzhou were studied in order to provide references for the application of shrub plants in the construction of sponge city.【Method】The maximum interception of leaves, the maximum interception of unit leaf area, the maximum interception of branch, and the maximum interception of canopy of Hibiscus rosa-sinensis, Bougainvillea glabra, Loropetalum chinense var. rubrum, Pittosporum tobira, Aglaia odorata and Fagraea ceilanica were measured by submerging method.【Result】The maximum interception of leaves of 6 landscape shrub plants was between 41.20-209.73 mg. The maximum interception of unit leaf area of 6 landscape shrub plants was between 6.84-15.80 mg/cm2. The maximum interception of branch of 6 landscape shrub plants was between 1.85-14.85 g. The maximum interception of canopy of 6 landscape shrub plants was between 406.49-3 204.04 g/m2. The interception of unit leaf area of L. chinense var. rubrum was the largest among 6 landscape shrub plants. The interception of leaves of B. glabra was the highest among 6 landscape shrub plants. F. ceilanica was the best one in blade water holding performance among 6 landscape shrub plants. Among the 6 landscape shrub plants, H. rosa-sinensis had the maximum interception of branch and the maximum interception of canopy. The maximum interception of leaves had a significantly positive correlation with leaf area in 6 landscape shrub plants. The maximum interception of canopy had a significantly positive correlation with maximum interception of branch in 6 landscape shrub plants.【Conclusion】Some landscape shrub plants with high canopy interception such as H. rosa-sinensis and some landscape shrub plants with high water holding performance such as F. ceilanica can be used in construction of sponge city to relieve the pressure of city water consumption and improve the ecological and sustainable development of Guangzhou City.